Kinerja Lapis Pondasi Semen Komposit Tanah Dengan Bahan Tambah Matos Soil Stabilizer Pada Ruas Entikong – Rasau 2 - Diana, Nur Ayu; Widodo, Teguh; Asep Syarip Hidayat (Universitas Muhammadiyah Surabaya, 2024)
The challenge of implementing a soil cement composite foundation layer (LFSKT) in Indonesia is the availability of soil crushing and soil cement mixing equipment as well as compaction equipment following SKh-2.5.4. especially in remote areas, and quarry soil with a grain content passing sieve no. 200 of less than 35% which met the required UCS value with a maximum cement stabilization of 8%, so additives were needed to achieve the required strength. This paper presents an evaluation of the performance of LFSKT with the addition of Matos soil stabilizer on the Entikong – Rasau 2 Sta. 75 + 000 up to Sta. 90+000. Laboratory mix design to determine the composition of the LFSKT material by carrying out free compression tests of soil-cement and soil-cement-matos mixture specimens. The stages of implementing LFSKT work in the field are carried out following S.Kh. 2.5.4. Free compressive strength tests of field mix, sand cone, and Dynamic Cone Penetrometer, DCP using the Scala Penetrometer were carried out to control the strength and homogeneity of LFSKT. The composition of LFSKT resulting from a laboratory mix design is 8% cement and 2% mate. Based on the UCS value of the field mixture, relative density, SPR and CBR determine the minimum effective thickness limit for LFSKT to meet the strength requirements according to SKh-2.5.4.